Floret Farm's cut flower garden : grow, harvest & arrange stunning seasonal blooms - Benzakein, Erin; Chai, Julie (Chronicle Books, 2017)
Welcome to the world of Floret Farm, where hundreds of flower varieties grow and thrive to produce show-stopping arrangements. Here, star flower farmer Erin Benzakein shares her insights on planting a cutting garden of your own - wherever you live. Learn the secrets to her airy and lush arrangements, including how-tos for spectacular bouquets, garlands, and wreaths to showcase your gorgeous flowers. Featuring planting, cultivating, and harvesting advice for more than 175 flower varieties along with tops to preserve their freshness from field to centerpiece, this book has everything you need to start planning your garden and the stunning arrangements that will keep your home bright and blooming year after year.--COVER.